PEMBELAJARAN KERAJINAN MENURUT KURIKULUM MUATAN LOKAL DI SLTP PENYELENGGARA PROGRAM KETERAMPILAN KERAJINAN DJ YOGYAKARTA - Martono Martono (Jurnal Cakrawala Pendidikan, 2001)
In developing the quality l?!'teaching crqfis in junior high school, LPM Universitas NegeriYogyakarta through the school developing program has done development which resulteddecreasing the gap jelt by the school. This program was done in the form ~f leaming activity,which has done by developing team from LPM UNY to the teachers and students in the school.Teachers as the prin1ary target of'handicraft skill development, in the next time are hoped thereis good improving the teaching crafts in the school it self. The actuating ofthe handicraft skillsin the class use the material that has outlined in the curriculum developed with local culturalmaterial. The aims ofteaching crqfts principally were to teach esthetic value, work appreciationthe basic offorming work ethos, the appreciation product toward teacher and student. Thetraining aims to analyze the curriculum ojj'unior high school crajis related the local culturalpotential,The teaching crafts in the class uses the materials guided in the curriculum that aredeveloped using the local culturallnaterials. The teaching materials involve: 1) wood crafts thatconsists oj" carving and bench working (constnlction): 2)Textil that consists oj" macrame,embroidery, printing, and batik; 3) ('feramic (earthen ware) that consists o.fforming, decorating,and burning; 4). Weaving (cane) that consists .flat cane work, and construction, and; 5).Drawing that consists oftechnical drawing, still life drawing, ornament, and color knowledge.The teaching strategy involve the student activity in cra..fis activities.The. result ofthis training shows that teaching and learning are cultural activities. Becousethey are cultural activities, they truth value, norm, and principle needs to be protected. The crafttraining in junior high school involves teachers and students in the realistic process, so theworking appreciation, craji product appreciation, and introduction oj'the local cultural cangrow. The result of the training been felt be teacher and student. Materially the students'production are proper and they can been sold. The teacher will add the knowledge and skills inorder to improving the teaching quality. The school get special attention through relationshipwith high education institution. l'he student also get knowledge and skills to continue the studyand they can be useful"lor society. The last aims oj'this training is that the children becomecreative, diligent, scrutinized, sensitive to the environment, and become independent.